Hybrid electrical air-cushion tracked vehicle for swamp peat in Malaysia - Rahman, Mohammed Ataur; Mohiuddin, A. K. M.; Yahya, Azmi (2008)
The aim of this paper is to present a hybrid electrical air-cushion tracked vehicle (HETAV). Mathematical models are incorporated with accounting the kinematics and dynamics behaviors of the vehicle. Sinkage of the HETAV is sensed by an ultrasonic displacement (UD) sensor in order to operate the air-cushion system. The air-cushion of HETAV is protected with a novel-design auto-adjusting supporting (AAS) system. A propeller is equipped with the vehicle to develop additional thrust for overcoming the dragging motion resistance of the air-cushion system . The performance of the HETAV is defined by traction and motion resistance. The mean value of traction for the swamp terrain with propeller over without propeller increases 10.21% and 6.47% for the vehicle weight of 1.02 kN and 2.04 kN, respectively. Similarly, it was found that the mean values of vehicle’s motion resistance decreases 12.63% and 25.81% for the vehicle weight of 1.02 kN and 2.04 kN, respectively.